Review on preliminary study on studentâs motivation in learning history - Baderi, M. (Springer, 2019)
Learning history is compulsory to every student in Malaysia. However, most of the students are not interested in this subject. This study aims to gather the preliminary data to investigate studentâs motivation in learning history and their perspective on integrating technology into the classroom. This study used convenience sampling technique (n = 83 students) and collected data through an instrument distributed among the students. The results indicate that the current materials for learning history are not sufficient and satisfactory. Therefore, this study proposed a new technology namely Virtual Reality technology in learning history and positive feedbacks received in incorporating this technology in learning history subject into the classroom. Â© Springer Nature Switzerland AG 2019.